2007
DOI: 10.1038/nature06189
|View full text |Cite
|
Sign up to set email alerts
|

Purine-mediated signalling triggers eye development

Abstract: A conserved network of eye field transcription factors (EFTFs) underlies the development of the eye in vertebrates and invertebrates 1 . To direct eye development, Pax6, a key gene in this network 2,3 , interacts with genes encoding other EFTFs such as . However, the mechanisms that control expression of the EFTFs remain unclear 7 . Here we show that purine-mediated signalling triggers both EFTF expression and eye development in Xenopus laevis. Overexpression of ectonucleoside triphosphate diphosphohydrolase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 34 publications
(40 reference statements)
4
92
0
2
Order By: Relevance
“…While we do not have specific information about the catalytic properties of ecto-nucleotidase isoforms expressed in zebrafish, assuming data from mammals and amphibian, the decrease in ATP hydrolysis seems here could involve NTPDase 2, due to hydrolysis ratio 30:1 (ATP:ADP) that contributes more effectively to ATP hydrolysis when compared with other NTPDases [15,49,50]. In fact, the expression of E-NTPDase 2 isoforms (entpd2a.1 and entpd2a) was significantly decreased in glucose-treated zebrafish.…”
Section: Discussionmentioning
confidence: 93%
“…While we do not have specific information about the catalytic properties of ecto-nucleotidase isoforms expressed in zebrafish, assuming data from mammals and amphibian, the decrease in ATP hydrolysis seems here could involve NTPDase 2, due to hydrolysis ratio 30:1 (ATP:ADP) that contributes more effectively to ATP hydrolysis when compared with other NTPDases [15,49,50]. In fact, the expression of E-NTPDase 2 isoforms (entpd2a.1 and entpd2a) was significantly decreased in glucose-treated zebrafish.…”
Section: Discussionmentioning
confidence: 93%
“…This behavior would potentially support platelet aggregation. Control of purinergic signaling by NTPDase2 has been implicated in the differentiation of stem cells in the nervous system (3,21) and was recently shown to be responsible for initiation of embryonic eye development (5). Both the processivity of NTPDase1 and the high ATPase:ADPase ratio of NTPDase2 depend on native interactions of the transmembrane domains (19,(22)(23)(24).…”
mentioning
confidence: 99%
“…Cellular responses are induced by binding to two classes of P2 receptors: G proteincoupled P2Y receptors and ligand-gated P2X ion channels (1)(2)(3)(4)(5)(6). The ''purinergic signaling'' effects are converted and terminated via successive dephosphorylation of the nucleotides by a cascade of membrane-bound enzymes (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…However, a role for ATP signalling is now evident [64]. Masse et al reported that overexpression of NTPDase2 in the anterior part of the embryo could induce ectopic eye formation-an effect that was increased by simultaneous overexpression of the P2Y 1 receptor.…”
Section: Eye Developmentmentioning
confidence: 99%
“…Note that ATP release does not occur at this time in the posterior location, although at later times, there is a clearly substantial ATP release in this location that may be involved in the control of the development of the future nervous system. Reproduced with permission from [64] simple sequential chain of gene activation, but involves both positive feedback from downstream genes to activate upstream genes and positive self-regulation of gene expression. Pax6 for example activates Six3, Lhx2 and tll, but these genes in turn upregulate expression of Pax6, which is also able to reinforce its own expression.…”
Section: Eye Developmentmentioning
confidence: 99%